Implication of interfacial tension reduction and wettability alteration by surfactant on enhanced oil recovery in tight oil reservoirs. (November 2022) - Liu, Xuefen; Kang, Yili; Yan, Lingling; Tian, Jian; Li, Jianfeng; You, Lijun
Abstract: Tight oil reservoir is usually characterized by poor physical properties with oil recovery less than 10%. The objective of the study is to investigate the effect of 4 different types of surfactants to change rock surface tension and interfacial tension as well as its impact on enhanced oil recovery (EOR) in tight oil reservoirs. Results shows that the fluoride FC-1 and GS surfactant has more potential for wettability alteration and interfacial tension reduction respectively. The interfacial tension decreased from 6.072 mN/m to 2.04 mN/m, 0.03 mN/m, 0.1 mN/m, and 0.04 mN/m under the action of FC-1,  GS surfactant, FC-2, and FC-3, respectively. FC-1 made the wettability changed from original hydrophilic or oil-hydrophilic to hydrophobic and oil-phobic. While the effect of wettability modification by other three was not so obvious and the contact angle was no more than 45 degrees. So, the GS and FC-1 was selected for displacement tests to investigate the effect in augmenting injection and enhancing oil recovery. The average reduction rate of injection pressure by fluoride and Gemini surfactant was 32.4% and 14.2%, respectively. Under the action of fluoride and GS surfactant, the water-phase permeability increased by 36.8% and 29.9%, respectively. The improvement of recovery mainly occurred in primary water flooding, while the amount of oil displaced by surfactant solution and secondary water flooding was little or even no, with the recovery efficiency improved by 0–8.4%. The effect of fluoride was more obvious, revealing that changing rock wettability is more favorable than reducing the interfacial tension for oil recovery in tight sandstone oil reservoirs.